ACCELERATING STUDENTS’ CAPABILITIES IN ACCOMPLISHING FINAL PAPERS: AN EVALUATION - Azhar, Fadly; Yuanita, Putri; Erni; Novitri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2021)
This paper aimed at evaluating such aspects as self-efficacy, research methodology, types of supervisor, and academic writing ability in accelerating students accomplishing final papers. 214 students of bachelor and master programs at Universitas Riau - Indonesia were selected through purposive sampling technique as the participants. This research used Context, Input, Process, and Product Evaluation Model to evaluate those variables. The research findings revealed that (a) there was no significant difference in self-efficacy on the aspects of gender and learning support facilities; (b) in research methodology on the aspect of gender; (c) in academic writing ability on the aspects of gender; and (d) in types of supervisors on the aspects of gender, sources of educational cost, and learning support facilities. However, (a) there was a significant difference in self efficacy on the aspects of the profession, and sources of educational cost; (b) in research methodology on the aspects of the profession, sources of educational cost, and learning support facilities (c) in academic writing ability on the aspects of the profession, sources of educational support, and learning support facilities; and (d) in types of supervisors on the aspect of the profession. In conclusion, self efficacy contributed 59.7%; research methodology 10.4% and types of supervisor 0.1% —- which is a totally of 70.2% towards the students’ academic writing ability in accelerating students accomplishing final papers.